Peran Strategi Pembelajaran Terhadap Hasil Belajar Peserta Didik - Imel Ahmarita Meliana; Marsofiyati Marsofiyati (Lembag, 2024)
This study seeks to determine in case there is a role of learning strategies on student learning outcomes. In this reserach, there is no population and sample involved, but rather using literature, such as thesis, articles, and books. The research used a qualitative approach with a correlation analysis method through literature studies using theses, articles, and books. Based on of several relevant journals, it can be said that learning strategies have an important role in maximizing student learning outcomes. In other words, the more effective the learning strategy applied, the more optimal the learning outcomes obtained.